Pembinaan dan Peningkatan Usaha Pengolahan Produk Makanan Jajanan Berbasis Ikan dan Sagu Di Desa Sungai Paku Kabupaten Kampar - Dewita Dewita; Yenita Roza; Andarini Diharmi; Syahrul Syahrul; Mirna Ilza (Unri Conference Series: Community Engagement, 2021)
Sungai Paku Village, Kampar Kiri sub-district, Kampar district, is one of the villages designated as a Village Assisted Village by LPPM, University of Riau, with the target group being women who are members of the UD business group. Mother's love. This business group was originally designed to produce fish and sago based snacks. Therefore, PKM activities are directed at fostering, developing and improving product quality that meets SNI standards. This solution will be offered to partners in order to develop their business and improve the quality of their products. The products that have been trained for several years before are fish sago noodles, meatballs, nuggets and fish snacks. Thus, this year's activity is a continuation of the activities of previous years, namely providing training to add product variants, so that PKM activities are emphasized on training on the manufacture of snack food products such as fish risoles and fish balls (fish balls). In this activity the team was accompanied by Kukerta Unri students in 2021 who were deployed in Sungai Paku Village consisting of 2 groups (the Balek Kampung Kukerta group and the Integration Kukerta group). The method of activity used is the extension and experiment method, namely processing sago and fish-based snacks (such as fish balls and risoles). with the implementation stages as follows: (1) The preparation stage, which is to approach partners and provide an explanation of the aims and objectives for carrying out PKM activities. and (2) the implementation stage, namely providing counseling and training to partners. Regarding the technology transfer for processing new variants of snacks such as fish balls and risoles. The outputs of this activity include: i) Increased public understanding of business management, ii) Identification of new business opportunities for fish-based processed products for partners, and iii) Publication on online (electronic) media in Pekanbaru Pos, as well as scientific articles for community service. seminars and publications in nationally accredited journals.